Security and integrity attacks in named data networking: A survey - Mohammad Shahrul Mohd Shah; Yu-Beng Leau; Mohammed Anbar; Ali Abdulqader Bin-salem (IEEE, 2023)
The notion of Information-Centric Networking (ICN) specifies a new communication model that emphasis on the content exchanged rather than the devices connected. ICN architectures like Content Centric Network (CCN) and Named Data Networking (NDN) have been proposed to shift from host-centric based to content-centric based communication along and provide benefits to users in addressing the challenges of traditional IP networks. It differs from host-centric standard Internet Protocol (IP) networking in of naming, routing, forwarding, and caching characteristics. Naming features used in NDN use global unique names provided by content-based security and encryption. It ensures content integrity and authenticity as part of its design. In this paper, we survey on security aspects of NDN/CCN, discussing three integrity attacks such as replay attacks, Man-in-The-Middle (MiTM) attacks, and Content Poisoning Attack (CPA) with countermeasure against them. In addition, we highlight an open challenge and offer future research directions in the context of security.